A Strategy for involving community forest managers in effective forest fire management in Nepal - Parajuli, Ashok; Gautam, Ambika P.; Sharma, Sundar; Lamichhane, Prakash; Sharma, Gagan; Bist, Bhuwan Singh; Aryal, Upendra; Basnet, Reecha (Banko Janakari, 2022)
Each year forest fire causes enormous damage to Nepal's forest ecosystems and landscape. For an active community involvement at the landscape level, policymakers must take the interests of local forest managers into account to increase social acceptability. This research explores the perception of community forest managers, who are constantly managing forests at the grassroots level, to understand the relationship between their priorities, needs, and attitudes toward forest fire management. Eighty–eight key informants from six districts were interviewed using a structured questionnaire. The questionnaire was divided into three major sections, (i) forest fuel management and infrastructure, (ii) forest fire management strategies and actions, and (iii) public education and awareness on forest fire management. The data were analyzed using the Kruskal–Wallis test, where the respondents rated above 4.2 out of 5 for activities like increase of insurance mechanisms, providing training for firefighting volunteer groups, and provisioning firefighting equipment. The majority of the respondents agreed on the activities under the forest fire management strategies and actions section (Kendall's Tau = 0.8501), followed by forest fuel management and infrastructure (Kendall’s Tau= 0.6757). We anticipate that the results of this study will be helpful for the local decision–makers in involving different communities and identifying their priorities while implementing various forest fire management activities in diverse landscapes or provinces of the country.